Policy Implementation of Rumah Dataku Development for Quality Family Village in Kiaracondong Sub-district, Bandung City, Indonesia - Astuti, Tika Dwi; Ramdani, Endah Mustika; Gedeona, Hendrikus Triwibawanto; Maulana, Riky Rinaldy (Universitas Muhammadiyah Yogyakarta, 2025)
Rumah Dataku is a vital component of the Kampung Keluarga Berkualitas (Quality Family Village) program, serving as a data center for population, health, and socio-economic information at the village/urban ward level. However, comparative studies on Rumah Dataku across different areas remain limited. This study aims to analyze the implementation of Rumah Dataku in Kampung KB Bintara and Kampung KB Sakura, Kiaracondong District, Bandung City, and provide strategic recommendations to improve program effectiveness. A descriptive qualitative approach was used, with data collected through interviews, observations, and document analysis. The study applies George C. Edward III’s policy implementation theory, focusing on communication, resources, disposition, and bureaucratic structure. Findings show that Kampung KB Sakura excels in human resources, equipment, and funding, while Kampung KB Bintara faces significant limitations. Both villages struggle with consistently applying Standard Operating Procedures (SOPs). The study recommends partnerships, regular training, and continuous evaluation to ensure the sustainability of Rumah Dataku.